Corrosion of SiC induced by Hastelloy N alloy and its corrosion products in LiF–NaF–KF molten salt. (August 2016) - Yang, Xinmei; Zhang, Dongsheng; Liu, Min; Feng, Shanglei; Xue, Wandong; Liu, Huajian; Yu, Guojun; Zhou, Xingtai; Xia, Huihao; Huai, Ping; Li, Zhijun; Lu, Yanling; et al.
Highlights: Effect of Hastelloy N alloy and corresponding corrosion products on the corrosion of SiC was studied. Ni in alloy can react with Si in salt to drive the corrosion of SiC by the formation of Silicide (Ni31 Si12, NiSi, ) on alloy. Corrosion product NiF2 can increase the corrosion of SiC. Raman spectrum indicates that Si in salt is in the form of [SiF6 ] 2− . Corrosion product CrF2 can drive the corrosion of SiC by the formation of carbide (Cr7 C3, CrC) on SiC. Abstract: Interaction between SiC and Hastelloy N alloy in LiF–NaF–KF salt was studied for the application of SiC to molten salt reactors. Results reveal that Hastelloy N alloy and its corrosion products can induce the corrosion of SiC in salt. Ni can react with Si in salt to form silicide (Ni31 Si12, NiSi). Cr 2+ can react with SiC to form carbide (Cr7 C3, CrC). Ni 2+ can cause SiC with a thickness of 50 μm almost disappear after 45 days; thus, the Si content in salt can increase to 0.5 wt%. Raman spectrum indicates that Si in salt is in the form of [SiF6 ] 2− .